Doing it for the team: Soccer coaches' identity leadership predicts players' effort, turnover intentions, and performance. (July 2021) - Krug, Henning; Haslam, S. Alexander; Otto, Kathleen; Safi, Gahis; Steffens, Niklas K.
Abstract: Objectives: The present research investigates how coaches' identity leadership predicts individual and team outcomes in soccer. Specifically, we tested hypotheses that coaches' identity leadership would be associated with players' perceptions of (a) higher team effort, (b) lower turnover intentions, (c) better individual performance, and (d) better team performance. In addition, we aimed to examine the relationship between coaches' identity leadership and increased team identification of players and the degree to which the associations of identity leadership with these various outcomes were mediated by players' strength of team identification. Design: We conducted a cross-sectional study of male soccer players in Germany. Method: The final sample consisted of 247 male soccer players nested in 24 teams that completed measures of their coaches' identity leadership, team identification, team effort, turnover intentions, and individual/team performance. Results: Analysis revealed a positive relationship between coaches' identity leadership and team effort, as well as individual and team performance. Moreover, coaches' identity leadership was associated with lower turnover intentions. There was also evidence that the relationships between identity leadership and the investigated outcomes were mediated by team identification. Conclusions: These findings support claims that coaches' identity leadership is associated with better individual and team outcomes because it helps to build a sense of 'we' and 'us' in the team they lead. Highlights: Coaches' identity leadership was associated with higher team functioning in soccer. Coaches' identity leadership predicted better individual and team performance. Players' increased team identification was identified as the underlying mechanism.